PENGARUH PERTUMBUHAN EKONOMI DAN INFLASI TERHADAP PENGANGGURAN TERBUKA DAN KEMISKINAN DI KOTA SAMARINDA - Amalia, Siti (Faculty of Economics and Business, University of Muhammadiyah Malang, 2014)
The purpose of this study was to determine the direct effect of economic growth and inflation against unemployment and poverty in Samarinda, to determine the direct effect of unemployment on poverty in Samarinda, and also the indirect effect of inflation on economic growth and poverty in Samarinda. Data analysis and hypothesis used in this study were path analysis method (Path Analysis Model). Based on the results of quantitative and qualitative analysis and hypothesis testing it can be generated the economic growth and inflation effect on unemployment in Samarinda. So that, government are expected to make better employment opportunities in order to reduce the number of unemployment in Samarinda.